2016
DOI: 10.3758/s13421-016-0629-4
|View full text |Cite
|
Sign up to set email alerts
|

Practice makes imperfect: Working memory training can harm recognition memory performance

Abstract: There is a great deal of debate concerning the benefits of working memory (WM) training and whether that training can transfer to other tasks. Although a consistent finding is that WM training programs elicit a short-term neartransfer effect (i.e., improvement in WM skills), results are inconsistent when considering persistence of such improvement and far transfer effects. In this study, we compared three groups of participants: a group that received WM training, a group that received training on how to use a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 48 publications
(54 reference statements)
1
6
0
Order By: Relevance
“…In the present research, the specific WM training effects on the 17 trained tasks among the participants of the experimental group were analyzed and the results showed significant gains on all the trained WM tasks from the pre to post-training assessments. This finding is similar to earlier studies which have reported evidence for substantial enhancements in the performance on the trained tasks with WM training (Guye, Simoni, & von Bastian, 2017;Matzen et al, 2016;von Bastian & Oberauer, 2014). Similar evidence on the improvements on the trained tasks have been reported among young-aged and old-aged adults (Karbach & Verhaeghen, 2014;Melby-Lervåg et al, 2016) and in our earlier research among middle-aged adults (Mridula et al, 2017;Namratha et al, 2017).…”
Section: Wm Training Effects On the Trained Taskssupporting
confidence: 92%
“…In the present research, the specific WM training effects on the 17 trained tasks among the participants of the experimental group were analyzed and the results showed significant gains on all the trained WM tasks from the pre to post-training assessments. This finding is similar to earlier studies which have reported evidence for substantial enhancements in the performance on the trained tasks with WM training (Guye, Simoni, & von Bastian, 2017;Matzen et al, 2016;von Bastian & Oberauer, 2014). Similar evidence on the improvements on the trained tasks have been reported among young-aged and old-aged adults (Karbach & Verhaeghen, 2014;Melby-Lervåg et al, 2016) and in our earlier research among middle-aged adults (Mridula et al, 2017;Namratha et al, 2017).…”
Section: Wm Training Effects On the Trained Taskssupporting
confidence: 92%
“…The issue of worse performance in the WMS visual memory task in group PA is more difficult to explain. The adoption of techniques and strategies that enhance performance in one cognitive domain but impair another, suggesting negative transfer ( 61 , 62 ), has been recently reported ( 63 ). There is not much further literature on this matter, especially not in the context of rtfMRI neurofeedback training.…”
Section: Discussionmentioning
confidence: 99%
“…There are different variants of the visual-imagery hypothesis, but the general idea is that when participants generate images for both common and bizarre items the images for the bizarre items are visually more distinctive (e.g., Black et al, 2012; Campos et al, 2009; Geraci et al, 2013; McDaniel & Einstein, 1986) or require more transformations in their creation that leads to better encoding for these items and, therefore, greater recall (e.g., Marshall et al, 1979; Wollen & Margres, 1987; see Worthen, 2006, for review). More generally, both ancient and modern writers propose that bizarre imagery enhances memory, and that the result is a bizarre imagery effect (e.g., Black et al, 2012; Burns, 1996; Buzan, 1991; Campos et al, 2008, 2009; Cornoldi et al, 1988; Dalgleish et al, 2013; Lorayne, 2010; Matzen et al, 2016; McDaniel & Einstein, 1986; Yates, 1966).…”
Section: Discussionmentioning
confidence: 99%
“…9-10). Modern self-help books for memory enhancement echo this ancient advice (Buzan, 1991;Lorayne & Lucas, 1974;Lorayne, 2010), as does recent research on memory therapeutics and memory training (Dalgleish et al, 2013;Dalgleish & Werner-Seidler, 2014;Matzen et al, 2016).…”
mentioning
confidence: 95%